Climate and plant controls on soil organic matter in coastal wetlands. (29th July 2018) - Osland, Michael J.; Gabler, Christopher A.; Grace, James B.; Day, Richard H.; McCoy, Meagan L.; McLeod, Jennie L.; From, Andrew S.; Enwright, Nicholas M.; Feher, Laura C.; Stagg, Camille L.; Hartley, Stephen B.
Abstract: Coastal wetlands are among the most productive and carbon‐rich ecosystems on Earth. Long‐term carbon storage in coastal wetlands occurs primarily belowground as soil organic matter (SOM). In addition to serving as a carbon sink, SOM influences wetland ecosystem structure, function, and stability. To anticipate and mitigate the effects of climate change, there is a need to advance understanding of environmental controls on wetland SOM. Here, we investigated the influence of four soil formation factors: climate, biota, parent materials, and topography. Along the northern Gulf of Mexico, we collected wetland plant and soil data across elevation and zonation gradients within 10 estuaries that span broad temperature and precipitation gradients. Our results highlight the importance of climate–plant controls and indicate that the influence of elevation is scale and location dependent. Coastal wetland plants are sensitive to climate change; small changes in temperature or precipitation can transform coastal wetland plant communities. Across the region, SOM was greatest in mangrove forests and in salt marshes dominated by graminoid plants. SOM was lower in salt flats that lacked vascular plants and in salt marshes dominated by succulent plants. We quantified strong relationships between precipitation, salinity, plant productivity, and SOM. Low precipitation leads to high salinity, which limits plant productivity and appears to constrain SOM accumulation. Our analyses use data from the Gulf of Mexico, but our results can be related to coastal wetlands across the globe and provide a foundation for predicting the ecological effects of future reductions in precipitation and freshwater availability. Coastal wetlands provide many ecosystem services that are SOM dependent and highly vulnerable to climate change. Collectively, our results indicate that future changes in SOM and plant productivity, regulated by cascading effects of precipitation on freshwater availability and salinity, could impact wetland stability and affect the supply of some wetland ecosystem services. Abstract : Coastal wetlands are among the most productive and carbon‐rich ecosystems on Earth. To anticipate and mitigate the effects of climate change, there is a need to advance understanding of environmental controls on coastal wetland soil organic matter (SOM). We investigated the influence of four soil formation factors: climate, biota, parent materials, and topography. We quantified strong relationships between precipitation, salinity, plant productivity, and SOM. Collectively, our results indicate that future changes in SOM and plant productivity, regulated by cascading effects of precipitation on freshwater availability and salinity, could impact wetland stability and affect the supply of some wetland ecosystem services.